Ecophysiological Responses of Cassava Plants (Manihot esculenta L. Crantz) Grown Under Saline Conditions to Elevated CO2 Levels - Siswandari, Puti
Cassava is an important agricultural commodity in Indonesia as an alternative staple food and raw material for feeds, industry, and biofuels. Efforts to develop cassava production continue, including the use of saline land. In addition to the planting of cassava in the saline field, the development of cassava production faces the problem of global warming as a result of the increase of CO2 levels in the atmosphere. The perspective of cassava production development also leads to conditions of environmental changes, so that the capacity of cassava plants can be known in the face of environmental stress.We investigated ecophysiological responses of cassava grown under saline conditions to elevated CO2. Four and six months old cassava plants were grown under saline conditions (100 mM, 50 mM and 0 mM NaCl solutions) and exposed to elevated CO2 level of 760 ppm, 580 ppm, and 370 ppm (ambient). After 30 days exposure to 50 mM NaCl and treated with elevated CO2 levels of 760 ppm, four months old cassava plant increased its dry weight (37%), total number of leaves (14,36%), catalase (CAT) activity (113,6%), and proline content in root (25%). Six months old cassava plants increased its number of leaves (70%), shoot height (62,66%), and proline content in root (37,5%) after exposure to 100 mM NaCl and treated with elevated CO2 levels of 760 ppm. In four months old cassava plants, storage root was formed at elevated CO2 levels of 760 ppm under 0 mM and 50 mM NaCl. In six months old cassava plants, storage root was formed in each treatment. The salinity stress condition caused the accumulation of Na+ ions in the root (6,1 ppm at 50 mM NaCl and 6,9 ppm under 100 mM NaCl). There was a tendency of the increase of stomatal resistance (0,02 s ?m-1) characterized by the stomatal closure in the leaves. Through the results of this study, elevated CO2 level of 760 ppm alleviated negative effect of 50 mM and 100 mM NaCl to plant growth.